2015
DOI: 10.1080/14763141.2015.1060253
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical jumping differences among elite female handball players with and without previous anterior cruciate ligament reconstruction: a novel inertial sensor unit study

Abstract: Persistent biomechanical and jumping capacity alterations have been observed among female athletes who have sustained anterior cruciate ligament (ACL) injuries. The purpose of this study was to examine if biomechanical jumping differences persist among a cohort of elite female handball players with previous ACL reconstruction several years after return to top-level competition. In order to achieve this goal, a direct mechanics simplified analysis by using a single Inertial Sensor Unit (IU) was used. Twenty-one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
(46 reference statements)
0
12
1
Order By: Relevance
“…Performance during CMJ tests has also been assessed using inertial devices that measure 47 vertical acceleration. [15][16][17][18] In addition to providing a measure of jump height, these devices can 48…”
Section: Introduction 34 35mentioning
confidence: 99%
“…Performance during CMJ tests has also been assessed using inertial devices that measure 47 vertical acceleration. [15][16][17][18] In addition to providing a measure of jump height, these devices can 48…”
Section: Introduction 34 35mentioning
confidence: 99%
“…The most recent advances in micro‐electromechanical systems have made magnetic inertial measurement units (MIMUs) a robust and reliable tool for sports motion analysis in the fields of performance evaluation and injury rehabilitation and prevention . A possible major advantage of MIMUs compared to force plate‐based procedures is that MIMUs enable non‐conditioned foot landing and outdoor testing, thereby allowing functional and unplanned movement analyses both in a laboratory and in field conditions.…”
Section: Introductionmentioning
confidence: 99%
“…22 Another study revealed differences in the duration of the propulsive phase during bilateral vertical drop jumps in ACL-reconstructed female handball players 6 years postsurgery. 43 …”
mentioning
confidence: 99%